Utilitarian Technological Solutions to Reduce CO2 Emission in the Aspect of Sustainable Development - Olejnik, Tomasz P.; Sobiecka, Elżbieta (Problemy Ekorozwoju, 2017)
The state of the environment is an important element of sustainable development. Emissions of greenhouse gases, including carbon dioxide, are monitored. Observed rise in CO2 emissions is forcing us to search for process solutions, which will significantly reduce its emissions, while meeting the economic criteria for the operation of the installation. EU legislation requires Member States to undertake research and implementation on industrial CO2 capture and processing. Filed under development refers to the guidelines of the European Commission, expressed in the document Towards an Integrated Strategic Energy Technology (SET) Plan: Accelerating the European Energy System Transformation. There are many innovative solutions related technologies CCS (Carbon Capture and Storage) operating on a laboratory scale and pilot plant. The most common methods that have found use in the binding of CO2 produced during the combustion process appropriate amine solvents, aqueous ammonia capture, absorption, ionic liquids, adsorption and membrane. Some of the above mentioned technology has been used application on the industrial scale after earlier financial calculations for their use and possible scenarios with process calculations based on value-to-cost criterion.